Fake bus stops for persons with dementia? On truth and benevolent lies in public health - Pauline Lorey (BMC, 2019)
Abstract Fake bus stops are one strategy to keep persons with dementia (PwD) from wandering. By setting up authentic looking shelters and benches in hallways or gardens, nursing homes create the illusion of bus stops, for the purpose of preventing wandering PwD from leaving the facility and getting lost. By attracting wandering PwD to sit down and wait for the bus, they can be supervised more easily by caregivers. However, concerns are expressed that the use of fake bus stops could cause more harm than good for PwD, due to their deceptive nature and the potential stigmatisation of individuals seated at a fake bus stop. This article discusses the ethical aspects of using fake bus stops and outlines considerations prior to setting up fake bus stops in nursing homes in keeping with good clinical practice in dementia care. Moreover, the article assesses whether or not fake bus stops can be ethically justifiable, and if so, how they can be ethically justified and implemented in Israeli and other facilities for PwD.